DEPRESI POST PARTUM DAN INVERTED NIPPLE GRADE 1 MENGHAMBAT PRAKTIK PEMBERIAN ASI : Postpartum Depression And Inverted Nipple Grade 1 Inhibit Breastfeeding Practices - Yoga, M Agung Prasetya Adnyana; Anggraini, Dian Isti; Saftarina, Fitria (Media Gizi Pangan, 2024)
Breast milk is the best food for infants because it contains complete nutritional values to support infant growth and development. However, anatomical abnormalities in the nipple such as inverted nipple and psychological factors of post partum depression affect the success of breastfeeding practices. This study was design to determine the effect of post partum depression and inverted nipple grade 1 on breastfeeding practices. This study was used a case study method with a nutritional needs management approach for breastfeeding mothers on respondents who breastfeed babies aged 16 months, the Edinburgh Postnatal Depression Scale (EPDS) questionnaire is used to assess post partum depression and if the EPDS score ≥ 10 then the mother is indicated to have post partum depression. Data regarding inverted nipple in mothers using secondary data. Food recall 1 x 2 4 hours was used to assess the mother's food consumption pattern followed by calculation of the level of nutrient fulfilment to quantitatively assess the mother's macronutrient intake in terms adequate or inadequate category. The total EDPS score was 13 so that the mother was included in post partum depression and based on secondary data and Aesthetic Surgery diagnosis guidelines, the mother was categorised as having inverted nipple grade 1. Both factors can hinder the continuity of breastfeeding practices. Support from husband and family as well as using the breast pump method on inverted nipples can help mothers to produce adequate amounts of breast milk. Quantitative analysis of the level of fulfilment of maternal nutrients in the adequate category, namely energy intake of 113% (good), protein intake of 113% (good), fat intake of 82% (moderate) and carbohydrate intake of 111% (good). Post partum depression and inverted nipple can inhibit breastfeeding practices, so premarital counselling and education about psychological disorders and anatomical abnormalities of the nipple during antenatal care (ANC) are needed for mothers and husbands to increase the success of breastfeeding practices for infants.